Women's involvement in local forest governance groups in Malawi: Scope for a randomized study on gender quota encouragement - Dulani, Boniface; Muthema, Funny; Kambuku, Flossy; Kosec, Katrina; Duchoslav, Jan (CGIAR System Organization, 2023)
It is important to understand the extent to which improved participation of women in local resource governance institutions can improve or otherwise change the functioning of these groups and, ultimately, environmental and socioeconomic outcomes. To this end, we conducted an exploratory study in rural Malawi to identify potential units for a future experimental intervention focused on randomly encouraging the enforcement of gender quotas to increase women’s involvement in local-level forest management. This scoping report provides background information on the de facto and de jour ways in which women participate in and influence these institutions.